Evaluating the Items of Trust Enhancement (TE) Measurement in the Manufacturing Organizations in Nigeria Through Exploratory Factor Analysis - Popoola Mufutau Olapoju; Naimot Folake Popoola (International Journal on Integrated Education, 2026)
The purpose of this study is to carry out instrument validation for the items of Trust Enhancement (TE) through exploratory factor analysis (EFA). The data gathering instrument employed is questionnaires, which were administered to employees in the manufacturing organization in Nigeria. 100 questionnaires were gathered to perform the EFA. The findings show that Bartlett’s Test of Sphericity is significant (P-Value < 0.05). Kaiser-Meyer-Olkin (KMO) is excellent as it surpasses the required value of 0.6. These two results (Bartlett’s Test, which is significant, and KMO > 0.6) suggest that the data is suitable in size. The Cronbach’s Alpha test was higher than 0.7 for all the items of the construct, this show that these items are all reliable. This research contributes to the domain of supply chain management by scrutinizing the items of the construct of Trust Enhancement (TE), which could improve performance in manufacturing organizations in Nigeria.